2013
DOI: 10.1371/journal.pone.0054300
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Protective MHC-I Haplotype Not Associated with Dominant Gag-Specific CD8+ T-Cell Responses in SIVmac239 Infection of Burmese Rhesus Macaques

Abstract: Several major histocompatibility complex class I (MHC-I) alleles are associated with lower viral loads and slower disease progression in human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) infections. Immune-correlates analyses in these MHC-I-related HIV/SIV controllers would lead to elucidation of the mechanism for viral control. Viral control associated with some protective MHC-I alleles is attributed to CD8+ T-cell responses targeting Gag epitopes. We have been trying to know the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…While macaque R03-013 experienced a transient viral rebound between weeks 16 and 32, it showed stringent control thereafter, and no SIV controllers experienced late-phase breakthrough infection. We previously noted that some 90-120-Ia ϩ and 90-010-Id ϩ naive macaques showed lower viral loads (19,20), but they only rarely become spontaneous aviremic controllers. This indicated that the passive NAb conferred robust SIV control.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…While macaque R03-013 experienced a transient viral rebound between weeks 16 and 32, it showed stringent control thereafter, and no SIV controllers experienced late-phase breakthrough infection. We previously noted that some 90-120-Ia ϩ and 90-010-Id ϩ naive macaques showed lower viral loads (19,20), but they only rarely become spontaneous aviremic controllers. This indicated that the passive NAb conferred robust SIV control.…”
Section: Resultsmentioning
confidence: 97%
“…We first retrospectively performed a longterm follow-up of previously SIV mac239 -infected, NAb-immunized rhesus macaques that showed undetectable set point viral loads (less than 4 ϫ 10 2 copies/ml) (17,19,20). Four pairs of rhesus macaques that were identified as sharing different MHC-I haplotypes (21) Counterparts had been passively infused intravenously with 300 mg of polyclonal anti-SIV neutralizing IgG at day 7 postinfection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations